Genetic variations in Thomas’s Rope Squirrel (Funisciurus anerythrus) and Gambian Sun Squirrel (Heliosciurus gambianus) Ibadan, Nigeria, using Allozyme markers (2018)
Thomas’s Rope Squirrel (Funisciurus anerythrus) and Gambian Sun Squirrel (Heliosciurus gambianus) are two of the eight squirrel species found in Nigeria with overlapping habitats in Southwestern Nigeria. Squirrels are involved in pollination, seed dispersal, vectors of human and domestic animal diseases as well as crop and household pests. These species and the crucial ecosystem services they render are threatened by habitat destruction, human encroachment and the fact that they are being used as a source of protein in Nigeria. Their conservation would be enhanced by availability of accurate genetic information which are scarce for these species. This study seeks to provide baseline data on genetic variation at three allozyme loci in the two species in University of Ibadan, Ibadan, Nigeria. Twenty-nine individual squirrels including eighteen F. anerythrus species and eleven H. gambianus were used in this study. These were obtained from the wild within the University of Ibadan. Observed and expected heterozygosity (Ho and He), Hardy Weinberg equilibrium (HWE), genetic distance between the species, and inbreeding coefficients were performed using POPGENE and Tools for Population Genetic Analyses (TFPGA). In F. anerythrus, Ho and He were 0.6092 and 0.5635, respectively, while, for H. gambianus, Ho and He were 0.6242 and 0.5745, respectively. There were no deviations from HWE in all the tested loci (p>0.05). Nei genetic distance between the species was 0.0070 and the populations showed fairly high level of outbreeding (FST = 0.0029 ± 0.0017). More robust genetic markers would be required to further ascertain the genetic status of the species.